"De-gendering" the civil status? A public law problem. (4th August 2020) - Osella, Stefano
Abstract: This article raises the problem of the inclusion of gender in the civil status of the person and argues that public lawyers are now called on to understand whether a genderless civil status is constitutionally permissible and desirable. Admittedly, this is not an easy task. Gender categories are deeply rooted in our legal systems. Arguably, they may prove necessary for the achievement of constitutionally grounded public interests and protect fundamental rights, such as equality between men and women. The task that public lawyers are faced with is further complicated by the affirmation of the right to gender recognition based on self-determination, and the inclusion of nonbinary genders in the law. These developments are indeed profoundly transforming the way in which gender is registered and controlled. Importantly, they put in doubt the effectiveness of gender as a criterion of legal categorization.